Diagnóstico sobre a institucionalização e o grau de efetividade do planejamento em municípios históricos: Diamantina e Tiradentes - Fernanda Pedrosa Lima (2008)
The work intends to focus its arguments and analyses on the city halls institucional capacity of the historical cities Diamantina and Tiradentes with relation the implementation of the instruments of city hall planning as a hypotheses of respect to lack of or little application in the social territorial reality, of the innumerable plans, programs and projects that had been elaborated in the City councils. These planning instruments mention the human, administrative and financial resources oriented toward the city hall public administration. Through several analyses acomplished by this work, it was possible to elaborate a diagnosis on the institutionalization and the degree of effectiveness of the city hallplanning in these two cities. One of the diagnosis results is that the deficiency in the institucional capacity of the city halls has collaborated for non-characterization of the city image, where new necessities and activities come to appear in the space, without articulating with the urban politics and preservation. In this context, the city comes to present as a cultural patrimony, where many local governors and enterprisers implement this concept in the improperly and irresponsible way. For exemple the preservation marketing produce spaces and constructions, that copy to the past ones, in order to increase the tourism and, consequently, the economic growth of restricted sectors of the society.